THE EFFECT OF DESCRIPTION, INTERPRETATION, AND EVALUATION (DIE) TECNIQUE ON THE SENIOR HIGH SCHOOL STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Yusniah Tampubolon and Sri Juriati Ownie (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study was aimed at investigating the effect of Description, Interpretation andEvaluation (DIE) Technique on the students achievement in writing descriptivetext. The research was conducted in experimental design. The subject of this studywas the 2013/2014 grade XI students of SMA N1 Tanjungpura. The sample thatwas involved in this research was 60 students that were chosen randomly, that ineach group there were 30 students. The experimental group was taught byapplying Description, Interpretation and Evaluation (DIE) Technique, whilecontrol group was taught by applying Lecture Method. The instrument used in thisstudy was an subjective test. The data were taken by administering the pre-testand post-test to both of experimental and control groups. The data were analyzedby using t-test formula, the analysis showed that the score of the students in theexperimental group was significantly higher than that of students in the controlgroup at the level of significance 0,5 with the degree of freedom (df) 58; the tobservedis 3,3 while the t-table is 2,00. To obtain the reliability of the test, thewriter used the Pearson Product Moment Formula. The result of the study showedthat the reliability of the test was 0,92. Therefore, the null hypothesis (Ho) isrejected.